Implementation of the Culturally Responsive Teaching Approach in Mathematics Learning Tools for Fraction Material Based on Traditional Food in Elementary Schools - Mustolih; Toha Nantra; Alan Hakim Permadi; Indah Wahyuni; Umi Farihah (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to explore the implementation of the Culturally Responsive Teaching (CRT) approach in mathematics learning tools for fraction materials based on traditional foods in elementary schools. This study employed a qualitative approach with a descriptive case study design involving a fifth-grade teacher and elementary school students. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldana. The findings revealed that the implementation of CRT through traditional food-based mathematics learning created more contextual, meaningful, and inclusive learning experiences. Traditional foods such as kue lapis, lemper, and apem helped students understand fraction concepts more concretely through cultural contexts closely related to their daily lives. The implementation of CRT also increased students’ engagement, classroom interaction, confidence, collaboration, and appreciation of local culture. In addition, teachers shifted their pedagogical role from information providers to facilitators who connected mathematical concepts with students’ cultural experiences. However, several challenges were identified, including limited instructional time, teachers’ readiness in integrating local culture, and limited culturally responsive learning resources. The novelty of this study lies in integrating culturally responsive pedagogy with traditional food-based mathematics learning tools specifically for fraction materials in elementary schools. This study contributes theoretically to the development of culturally responsive mathematics pedagogy and practically provides an alternative contextual mathematics learning model for elementary education.